Peningkatan Motivasi dan Hasil Belajar Matematika Siswa Kelas X SMA Negeri 2 Medan melalui Model Problem-Based Learning berbantuan teknologi Quiziz - Agustina Aritonang; Pandu Prabowo Warsodirejo; Hasda Tanty (Journal on Education, 2025)
This research aims to increase the motivation and mathematics learning outcomes of class X students at SMA Negeri 2 Medan through the application of the model Problem-Based Learning (PBL) combined with the use of Quizizz technology. This research uses the Classroom Action Research (PTK) method with the Kemmis and McTaggart model, which consists of four stages: planning, implementation, observation and reflection. The research subjects were 36 class X students, with instruments in the form of observation sheets, questionnaires and tests. The research results show that the implementation of PBL assisted by Quizizz is effective in increasing student motivation and learning outcomes. In the first cycle, 77.78% of students showed high learning motivation, and this figure increased to 100% in the second cycle. Improvements in student learning outcomes were also seen in cognitive, affective and psychomotor aspects, which experienced significant increases from the first cycle to the second cycle. The PBL model allows students to be more active in learning by presenting contextual mathematical problems, so that abstract material becomes easier to understand. In addition, the use of Quizizz creates an interactive and fun learning atmosphere through game elements. This research concludes that the application of PBL assisted by Quizizz is not only able to improve student learning outcomes holistically, but also motivates them to actively participate in learning. This approach is relevant for improving the quality of mathematics learning, especially in the digital era